Optimization of Bump Fairing in DLR-F6 Aircraft Related to Coefficient of Drag Using Simulation and Design of Experiment Method - Gabriel Jeremy Gotama; Fandi Dwiputra Suprianto; Teng Sutrisno (Petra Christian University, 2016)
Fairing is an aircraft component which is responsible in reducing drag force. By reducingthe coefficient of drag, drag force will be reduced and aircraft fuel consumption will be leaner. Abump fairing FX2 was designed by Vassberg for DLR-F6 aircraft. The design process doesn’tinvolve coefficient of drag effect. This research focuses in optimizing bump fairing FX2 by reducingthe coefficient of drag produced for DLR-F6 aircraft. Optimization was done by changing thedimension value of chord, span and thickness. Optimization method used in this research was 2kfactorial Design of Experiment (DoE) with Computational Fluid Dynamic (CFD) for acquiringdata.The result of the research shows that bump fairing FX2 can be optimized, although not byutilizing the 2kfactorial design of experiment. This is caused by the assumption of linear functionin 2k factorial. In this research, it was discovered that the function of chord, span and thicknessrelated to coefficient of drag is non-linear. Even though 2kfactorial was unable to be used tooptimize bump fairing FX2, the results are able to show correlation between variables and whichvariable are important. The highest reduction of coefficient of drag value was achieved by 8.75drag count.